Pseudo-thrombotic microangiopathy due to folate deficiency. Issue 1 (20th January 2023) - Larkin, Emily; Konkol, Samuel; Geraghty, Meghan
Abstract : Classically, deficiencies of vitamin B12 and folate are associated with megaloblastic anaemia. Additionally, vitamin B12 is able to cause a haemolytic anaemia in the form of pseudo-thrombotic microangiopathy (pseudo-TMA). Here, we present a case of a middle-aged woman with a history of Roux-en-Y gastric bypass who presented with dyspnoea and fatigue and was found to have thrombocytopenia and a non-immune haemolytic anaemia. Work-up for haemolytic uraemic syndrome, thrombotic thrombocytopenic purpura, paroxysmal nocturnal haemoglobinuria, infection, malignancy and autoimmune conditions was unremarkable. Her haemolytic anaemia and thrombocytopenia resolved with folate replenishment. She was diagnosed as likely having pseudo-TMA secondary to folate deficiency.